Analysis of the experience of managing the development of giftedness in the education system - Karkulova, А.А.; Satanov, A.B.; Zhumageldi, N.M.; Shakeyev, S.S. (BUKETOV BUSINESS REVIEW, 2023)
Object: Based on the analysis of managerial experience in the development of giftedness in the education system of foreign countries, the article describes the models for the development of the education of gifted children adopted in the developed countries of the world. A working understanding of giftedness is defined at the present stage of the practice of implementing the education of the gifted in the conditions of Kazakhstani practice in the context of a specialized education system for gifted children. The possibility of using adapted organizational conditions for the development of specialized educational institutions for gifted children is substantiated. Methods: Theoretical analysis of foreign research materials on the problem of the development of education for gifted children, analysis of the legislative framework of the Republic of Kazakhstan on the research problem. Findings: The analysis of theoretical materials made it possible to identify the presence of problem areas – the lack of a unified understanding of giftedness in science, which led to the existence in practice of a large number of educational models for the development of gifted children in the developed countries of the world. The grounds for understanding giftedness in Kazakh science are revealed. We believe that the definition of giftedness should have a functional characteristic, which allows using an activity approach in working out a model for the development of the education of gifted children, as well as taking into account the direction of development of the activities of gifted people, focused on the tasks set for the development of state programs. Conclusions: An analysis of models for the effective development of the education of gifted children, implemented in the developed countries of the world, is presented. We believe it is possible to develop an adaptive development model of the Kazakh model for the development of education for gifted children.